2018
DOI: 10.2188/jea.je20170065
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone or With Others and Depressive Symptoms, and Effect Modification by Residential Social Cohesion Among Older Adults in Japan: The JAGES Longitudinal Study

Abstract: BackgroundThere is little longitudinal evidence on the impact of specific living arrangements (ie, who individuals live with) on mental health among older adults, and no studies have examined the modifying effect of residential social cohesion level on this association. We aimed to examine the association between living arrangements and depressive symptoms and whether this association varies with residential neighborhood social cohesion level among 19,656 men and 22,513 women aged 65 years and older in Japan.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 31 publications
5
64
2
Order By: Relevance
“…Thus, our previous ecological observation might reflect not the contextual effect but the compositional effect of community-level social cohesion and reciprocity toward income-based inequality in depressive symptoms ( Haseda et al, 2018 ). The results of the present study were not in line with another study based on JAGES, which suggests that neighborhood social cohesion could alleviate the negative effect of living alone ( Honjo et al, 2018 ). This might happen because the gap of prevalence in depressive symptoms would be wider among different living arrangements than among different income groups, which could indicate the clear protective effect of community-level social cohesion.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, our previous ecological observation might reflect not the contextual effect but the compositional effect of community-level social cohesion and reciprocity toward income-based inequality in depressive symptoms ( Haseda et al, 2018 ). The results of the present study were not in line with another study based on JAGES, which suggests that neighborhood social cohesion could alleviate the negative effect of living alone ( Honjo et al, 2018 ). This might happen because the gap of prevalence in depressive symptoms would be wider among different living arrangements than among different income groups, which could indicate the clear protective effect of community-level social cohesion.…”
Section: Discussioncontrasting
confidence: 99%
“…After stratification by gender, odds ratios (ORs) of the presence on outcome were estimated using a multivariable logistic regression analysis, to analyze whether the living arrangement at baseline was associated with the decline in functional capacity after 3 years. The reference category was "with spouse only," based on previous studies [17,30]. The reason for stratification by gender in the analyses is that there was a statistically significant interaction between living arrangement and sex on the outcome (p for interaction = 0.014 in the crude model).…”
Section: Discussionmentioning
confidence: 99%
“…Cohesive communities might help residents to express trust towards their neighbours and to be psychologically healthier. Previous studies have revealed that neighbourhood social cohesion positively affected older people’s subjective well-being,35 36 and that cohesive communities prevented the occurrence of depressive symptoms in older people who lived alone and were at high risk of functional disability 37. Thus, we considered high levels of community social cohesion to be potentially protective against the onset of functional disability via the positive effects on psychological health, such as enhancing subjective well-being and inhibiting depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A cohesive community might be helpful in building new connections and encouraging social participation, which may keep men healthier and improve their psychological well-being. Honjo et al reported that rich social cohesion in a community buffered the risk of depression among older men living alone in Japan 37. Thus, community cohesiveness may protect men’s psychological health by helping them to build new connections in the community after retirement.…”
Section: Discussionmentioning
confidence: 99%